2017
DOI: 10.1371/journal.pgen.1007137
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the cohesin-loading factor NIPBL: Role of the lncRNA NIPBL-AS1 and identification of a distal enhancer element

Abstract: Cohesin is crucial for genome stability, cell division, transcription and chromatin organization. Its functions critically depend on NIPBL, the cohesin-loader protein that is found to be mutated in >60% of the cases of Cornelia de Lange syndrome (CdLS). Other mutations are described in the cohesin subunits SMC1A, RAD21, SMC3 and the HDAC8 protein. In 25-30% of CdLS cases no mutation in the known CdLS genes is detected. Until now, functional elements in the noncoding genome were not characterized in the molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…Altogether, these results corroborate the hypothesis that the NIPBL c.39dup transcripts do not undergo nonsense-mediated mRNA decay in NIPBLΔN cells and, instead, suggest the existence of a feedback mechanism between NIPBL protein and transcript to fine-tune its expression in order to ensure proper execution of its functions. A similar compensation mechanism is also observed in cell lines of patients with mutations in NIPBL, where the wild type allele is frequently upregulated, presumably in order to compensate for the downregulation of the mutant transcript induced by nonsense-mediated mRNA decay 28,33 .…”
Section: Nipbl Mrna Level Is Upregulated In Nipblδn Cellsmentioning
confidence: 60%
See 1 more Smart Citation
“…Altogether, these results corroborate the hypothesis that the NIPBL c.39dup transcripts do not undergo nonsense-mediated mRNA decay in NIPBLΔN cells and, instead, suggest the existence of a feedback mechanism between NIPBL protein and transcript to fine-tune its expression in order to ensure proper execution of its functions. A similar compensation mechanism is also observed in cell lines of patients with mutations in NIPBL, where the wild type allele is frequently upregulated, presumably in order to compensate for the downregulation of the mutant transcript induced by nonsense-mediated mRNA decay 28,33 .…”
Section: Nipbl Mrna Level Is Upregulated In Nipblδn Cellsmentioning
confidence: 60%
“…NIPBL expression was assessed with two different antibodies, one raised against its N-terminus and one recognizing its C-terminus. Notably, mutant NIPBL transcripts partially Page 6 on 47 undergo nonsense-mediated mRNA decay in cell lines of patients with heterozygous truncating variants in NIPBL; consequently, the corresponding truncated protein is unlikely to be detected 32,33 .…”
Section: Cells With a Homozygous Loss-of-function Mutation In Nipbl Ementioning
confidence: 99%
“…Similarly, Go analysis in the present study indicated enrichment of the genes in the yellow module in synaptic guidance. among the genes in the turquoise module, niPBl plays a critical and regulatory role in cohesion loading on chromatin, as well as having roles in gene expression and transcriptional signaling (33,34). Zinc finger protein 609 may participate in the regulation of cortical neuron migration (35).…”
Section: Discussionmentioning
confidence: 99%
“…The relatively large proportion (12 out of 40) of antisense RNAs is consistent with a previous report that antisense transcripts are highly prevalent in the human genome [29]. The list of 16 lncRNA genes includes beaver orthologs for well-known lncRNAs such as XIST [2] (which was the longest of 187 high-confidence lncRNA contigs at 3967 nt), maternally expressed gene 3 (MEG3) [30], terminal differentiation-induced noncoding RNA (TINCR) [31], and nipped-B homolog (Drosophila) long noncoding RNA bidirectional promoter (NIPBL-DT) [32].…”
Section: Beaver Orthologs Of Known Lncrnas or Known Noncoding Transcrmentioning
confidence: 99%